Smoking treatment optimisation in pharmacies (STOP): a cluster randomised pilot trial of a training intervention. Issue 1 (December 2017) - Madurasinghe, V.; Sohanpal, Ratna; James, Wai; Steed, Liz; Eldridge, Sandra; Taylor, SJC; Griffiths, C.; Walton, Robert
Abstract Background UK government policy aims to strengthen the role of community pharmacies in health promotion. Thus, we conducted feasibility studies for an intervention to enhance delivery of the NHS Smoking Cessation Service. Methods The overall aims were to assess acceptability and feasibility of conducting the intervention in community pharmacies and piloting this with a cluster randomised trial. Specific objectives were (1) to estimate likely participation rates of pharmacies and stop smoking advisors, (2) to establish the potential impact of the training intervention on throughput and retention of smokers in smoking services, (3) to establish potential impact on smoking cessation outcomes, (4) to optimise logistics for conducting a cluster randomised trial in the next phase of the research programme and (5) to consider the feasibility of collecting pharmacy and service user data. In this cluster randomised parallel group pilot trial, 12 community pharmacies in East London were allocated to intervention or usual practice using simple randomisation (allocation ratio 2:1). Data were analysed descriptively. Results Twelve of 54 (22.2%, 95% CI 12.0% to 35.6%) pharmacies and 20 of 23 (87.0%, 95% CI 66.4% to 97.2%) advisors invited, agreed to participate. Over 5 months, 302 smokers in intervention pharmacies (mean per pharmacy 43.1, 95% CI: −4.3 to 90.5) and 319 in usual practice pharmacies (mean per pharmacy 79.8, 95% CI: 19.0 to 140.5) joined the service. 51 of 621 smokers (6.3% in intervention vs 10.0% in usual practice) consented to provide additional data on smoking cessation. 17 of 19 smokers that consented were retained at 4 weeks in intervention arm (89.5%, 95% CI: 66.9% to 98.7%) and 24 of 32 in usual practice (75.0%, 95% CI: 56.6% to 88.5%). 10 of 19 in the intervention arm (52.6%, 95% CI: 28.9% to 75.6%) stopped smoking compared to 7 of 32 in usual practice arm (21.9%, 95% CI: 9.3% to 40.0%). The pilot was useful in providing insights on how best to conduct the definitive trial and shortcomings of our present logistical arrangements, including feasibility of collecting pharmacy and service user data. Conclusions Recruitment rates show that the main trial is feasible, and the results suggest that the intervention may improve retention and quit rates in smoking cessation services. We gained insights on how best to conduct the definitive trial which will proceed as planned.